Consumer Preferences for Attribute Selection of White Organic Rice Products in Pontianak City - Nur Inda Sari; Siti Sawerah; Sri Umiyati (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
Rice is a staple food for the majority of the Indonesian population. The extremely high dependency of Indonesian society on rice will become a problem if its availability can no longer be met. The high consumer demand for organic rice in Indonesia is a critical point, making it necessary to understand consumer preferences for purchasing organic rice to inform traders and producers. The objective of this research is to analyze consumer preferences for the selection of attributes of organic rice products in the city of Pontianak. This study utilized primary data obtained from interviews with 50 consumers of organic rice in Pontianak City. The data were analyzed using the conjoint analysis in SPSS. The results indicate that the combination of attributes most preferred by consumers for organic rice in Pontianak City is: organic rice type utility value 0.92; clear white color utility value 0.60; vacum packaging utility value 0.19; with claims of being soft sticky and soft texture and possessing Indonesian organic certification utility value 0.36); Recommendations are provided for business actors and researchers in the food commodity sector to support the development of organic rice in Pontianak City versi indonesia.